Fixation of mandibular fractures with 2.0-mm miniplates: review of 191 cases - Cabrini Gabrielli, Marisa Aparecida [UNESP]; Real Gabrielli, Mário Francisco; Marcantonio, Elcio; Vieira, Eduardo Hochuli [UNESP] (American Association of Oral and Maxillofacial Surgeons J Oral Maxillofac Surg, 2003)
Our goal was to study the use of 2.0-mm miniplates for the fixation of mandibular fractures. Records of 191 patients who experienced a total of 280 mandibular fractures that were treated with 2.0-mm miniplates were reviewed. One hundred twelve of those patients, presenting 160 fractures, who attended a late follow-up were also clinically evaluated. Miniplates were used in the same positions described by AO/ASIF. No intermaxillary fixation was used. All patients included had a minimum follow-up of 6 months. Demographic data, procedures, postoperative results, and complications were analyzed. Mandibular fractures occurred mainly in males (mean age, 30.3 years). Mean follow-up was 21.92 months. The main etiology was motor vehicle accident. The most common fracture was the angle fracture (28.21%). Twenty-two fractures developed infection, for an overall incidence of 7.85%. When only angle fractures are considered, that incidence is increased to 18.98%. Although only 1 patient (0.89%) described inferior alveolar nerve paresthesia, objective testing revealed sensitivity alterations in 31.52% of the patients who had fractures in regions related to the inferior alveolar nerve. Temporary mild deficit of the marginal mandibular branch was observed in 2.56% of the extraoral approaches performed and 2.48% presented with hypertrophic scars. Incidence of occlusal alterations was 4.0%. Facial asymmetry was observed in 2.67% of the patients, whereas malunion incidence was 1.78%. Fibrous union, mostly partial, occurred in 2.38% of the fractures, but only 1 of those presented with mobility (0.59%). Condylar resorption developed in 6.25% of the fixated condylar fractures. Mean mouth opening was 42.08 mm. The overall incidence of complications, including infections, was similar to those described for more rigid methods of fixation.